If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 120 + -30 + 6x = 2x + -60 Combine like terms: 120 + -30 = 90 90 + 6x = 2x + -60 Reorder the terms: 90 + 6x = -60 + 2x Solving 90 + 6x = -60 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 90 + 6x + -2x = -60 + 2x + -2x Combine like terms: 6x + -2x = 4x 90 + 4x = -60 + 2x + -2x Combine like terms: 2x + -2x = 0 90 + 4x = -60 + 0 90 + 4x = -60 Add '-90' to each side of the equation. 90 + -90 + 4x = -60 + -90 Combine like terms: 90 + -90 = 0 0 + 4x = -60 + -90 4x = -60 + -90 Combine like terms: -60 + -90 = -150 4x = -150 Divide each side by '4'. x = -37.5 Simplifying x = -37.5
| -41=-0.4(45n+60)+n | | -10x+2y+10=0 | | 2x-13=13-8x+14 | | -1+6x-6=23 | | 3y-5x=x+9 | | 5x-2/3-6 | | x^2+14-7=0 | | 6n+n=2860 | | 0.2x+5.7+4.9=10.2266 | | 4a+r= | | 26x-24=56 | | v^2=2 | | g-78=876 | | 6c-8-2c=-7 | | 0.17x-0.4(x+1700)=-2556 | | 20/0= | | 2t+2.2H=-3.7 | | X-108=36 | | x+3y-3z=-26 | | 2(6x+8)-2(3x-6)= | | 3x-8=-2(4x-2) | | H-3.5=5 | | 9(-5/8) | | 23.42-x=15.42 | | 4.12-c=2.45 | | -8x-14y=52 | | 4x+34+6x-14=180 | | 1-3/2x=5/6 | | 7x-(2x+5)=3x+7 | | -6+7x-4x=15 | | 78=6x+6 | | x+11.5=20.5 |